If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2y = 2 Solving 6x + 2y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 6x + 2y + -2y = 2 + -2y Combine like terms: 2y + -2y = 0 6x + 0 = 2 + -2y 6x = 2 + -2y Divide each side by '6'. x = 0.3333333333 + -0.3333333333y Simplifying x = 0.3333333333 + -0.3333333333y
| 3x-(-6)=24 | | x^2-35-2x=0 | | (5b-3)(5b+3)= | | (5b-3)x(5b+3)= | | 76=2(6+2w) | | 76=2w+2(6+2w) | | (5b-3)*(5b+3)= | | (5b-3)= | | 4a-3=7 | | (9+n)6=7(n-4) | | 4x^3-64x^2+240x=0 | | x^2-96=0 | | x^2-96=0 | | 7x-y=-25 | | 4y+4(-2)=12 | | 4y+4(-9)=12 | | y=2(1)-3 | | y=2(0)-3 | | y=2(-1)-3 | | y=4(2)+5 | | 4x-5=x-20 | | y=4(-1)+5 | | y=4(-6)+5 | | y+2(5)=-9 | | y+2(2)=-9 | | kx^2-10x+25=0 | | -4y+2y=2y-6+y | | 49v^4-16t^2=0 | | y=-6(1) | | y=-6(0) | | y=-6(-1) | | y=-2(-6)-6 |